PENGEMBANGAN JARINGAN INFORMASI PRODUKSI UNTUK PENINGKATAN KUALITAS EKSPORT JAMUR KUPING (AURICURARIA POLYTRICHA - Suwondo, Endy (LPPM UGM, 2002)

(untitled)
A development of information network through a construction of information network web base of mushroom production was utilized as one of development efforts of a complete information mushroom commodity and production available in ‘Lancar’ mushroom cooperation, Yogyakarta. Basis data on a web base executed via internet were integrated as a whole application providing a two-way treaffic information output between users and the cooperation management. This means there allowed access needed through which the both sides needs would be syncrhronised. The web base constructed as a frame of application programs on the mushroom data base management system provided facilities such as data updating and editing by the administration The on-line generated information could help supproting the need and importance of the information network at farmer groups level up to merket level. Information system of web base mushroom production was constructed and designed by Personal Home Page (PHP) programming and data base MySQL (Structure Query Language)